Clinical Utilization of Chimeric Antigen Receptor T Cells in B Cell Acute Lymphoblastic Leukemia: An Expert Opinion from the European Society for Blood and Marrow Transplantation and the American Society for Blood and Marrow Transplantation - Kansagra, Ankit J.; Frey, Noelle V.; Bar, Merav; Laetsch, Theodore W.; Carpenter, Paul A.; Savani, Bipin N.; Heslop, Helen E.; Bollard, Catherine M.; Komanduri, Krishna V.; Gastineau, Dennis A.; Chabannon, Christian; Perales, Miguel A.; et al. (Biology of Blood and Marrow Transplantation, 2019)
On August 30, 2017 the US Food and Drug Administration approved tisagenlecleucel (Kymriah; Novartis, Basel, Switzerland), a synthetic bioimmune product of anti-CD19 chimeric antigen receptor T cells (CAR-T), for the treatment of children and young adults with relapsed/refractory B cell acute lymphoblastic leukemia (B-ALL). With this new era of personalized cancer immunotherapy, multiple challenges are present, ranging from implementation of a CAR-T program to safe delivery of the drug, long-term toxicity monitoring, and disease assessments. To address these issues experts representing the American Society for Blood and Marrow Transplant, the European Society for Blood and Marrow Transplantation, the International Society of Cell and Gene Therapy, and the Foundation for the Accreditation of Cellular Therapy formed a global CAR-T task force to identify and address key questions pertinent for hematologists and transplant physicians regarding the clinical use of anti CD19 CAR-T therapy in patients with B-ALL. This article presents an initial roadmap for navigating common clinical practice scenarios that will become more prevalent now that the first commercially available CAR-T product for B-ALL has been approved.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Chimeric antigen receptor; Leukemia; T cell